2009
DOI: 10.1109/led.2009.2034115
|View full text |Cite
|
Sign up to set email alerts
|

Nitrided Tetragonal $\hbox{ZrO}_{2}$ as the Charge-Trapping Layer for Nonvolatile Memory Application

Abstract: Employment of a tetragonal ZrO 2 film as the chargetrapping layer for nonvolatile memory was investigated and the NH 3 nitridation effect of the ZrO 2 film on memory performance was also explored in this letter. The permittivity of the tetragonal ZrO 2 film is slightly reduced from 38.7 to 36.9 after nitridation; nevertheless, nitridation introduces more trapping sites and passivates the grain boundary channel which results in a high operation speed in terms of 2.6-V flatband voltage shift by programming at +1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…To solve these problems in SONOS type CTF memory, CTF memory devices using high-k materials such as HfO 2 , Al 2 O 3 , ZrO 2 , etc., have been developed in recent years. [9][10][11][12][13][14][15] These devices can provide large band offset with respect to Si, high trap density, and small equivalent oxide thickness (EOT). Therefore, the CTF memory device with high-k film is expected to offer better device performance as compared to the conventional CTF device with Si 3 N 4 film.…”
mentioning
confidence: 99%
“…To solve these problems in SONOS type CTF memory, CTF memory devices using high-k materials such as HfO 2 , Al 2 O 3 , ZrO 2 , etc., have been developed in recent years. [9][10][11][12][13][14][15] These devices can provide large band offset with respect to Si, high trap density, and small equivalent oxide thickness (EOT). Therefore, the CTF memory device with high-k film is expected to offer better device performance as compared to the conventional CTF device with Si 3 N 4 film.…”
mentioning
confidence: 99%
“…[2][3][4] On the other hand, ZrO 2 shows similar dielectric properties as HfO 2 but has higher k value ($37). 5 Consequently, there is an increasing interest in exploring ZrO 2 as CTL. 5,6 Wu et al studied the charge-trapping characteristics of ZrO 2 with and without nitridation and found that MONOS device with nitrided ZrO 2 showed better performance than that without nitridation due to nitrogen passivation of the ZrO 2 film.…”
mentioning
confidence: 99%
“…5,6 Wu et al studied the charge-trapping characteristics of ZrO 2 with and without nitridation and found that MONOS device with nitrided ZrO 2 showed better performance than that without nitridation due to nitrogen passivation of the ZrO 2 film. 5 Besides nitrogen, fluorine is also an excellent passivant to remove oxide defects and strengthen the dielectric films due to its very high electronegativity. 9 Therefore, fluorination is an effective way to improve the charge-trapping characteristics of dielectrics.…”
mentioning
confidence: 99%
“…Worth to be mentioned is that insignificant leakage current change can be obtained after RTA. The leakage current of annealed samples is much lower than that reported in [3] and it can be ascribed to the amorphous phase of the (ZrO 2 ) x (La 2 O 3 ) 1-x alloy which does not have grain boundary induced leaky paths as a crystalline dielectric [6][7].…”
mentioning
confidence: 69%